Seni Sasak Lombok sebagai Penggerak untuk Pengembangan Pariwisata Desa Wisata Setanggor - jumaidin jumaidin; Maisarah (Jurnal Pariwisata Nusantara (JUWITA), 2022)
The purpose of this study was to determine the art of Sasak Lombok as a driving force for the development of tourism in the tourism village of Setanggor. One of the developments that needs to be done is the revival of the cultural arts of the Lombok people which are increasingly less attractive to the younger generation, especially in theater arts, one example of theater art in Setanggor Village is usually Setanggor theater art performed at night with the aim of entertaining the bridegroom at the party. weddings in the island of lombok in particular. Central Lombok Regency With the rapid development of tourism, especially with the construction of the Mandalika City project and the construction of the Mandalika Moto Grand Prix racing circuit, it is hoped that this can be a driving force to improve the welfare of the people of Central Lombok in particular and the people of West Nusa Tenggara in general. Research data obtained through documentation and interviews. The sample used in the study were several stakeholders and the community involved in the Setanggor tourism village art studio. The results of this study are expected to provide information and education for the Indonesian people, especially the island of Lombok and tourists both domestically and internationally. The data obtained were processed using qualitative descriptive analysis. Qualitative analysis uses data analysis, data collection, data reduction and conclusion drawing/verification. So that the results of sequential research are clear and thorough. The results of qualitative descriptive analysis indicate that there is development carried out by the community and stakeholders involved in the development of the art of Sasak theater in the tourism village of Setanggor.